Crystal structures of FolM alternative dihydrofolate reductase 1 from Brucella suis and Brucella canis. Issue 1 (17th December 2021) - Porter, Imani; Neal, Trinity; Walker, Zion; Hayes, Dylan; Fowler, Kayla; Billups, Nyah; Rhoades, Anais; Smith, Christian; Smith, Kaelyn; Staker, Bart L.; Dranow, David M.; Mayclin, Stephen J.; et al.
Abstract : Crystal structures of FolM alternative dihydrofolate reductase 1 from Brucella suis and Brucella canis reveal prototypical NADPH‐dependent short‐chain reductases with structural similarity to protozoan pteridine reductases that are potential drug targets. Abstract : Members of the bacterial genus Brucella cause brucellosis, a zoonotic disease that affects both livestock and wildlife. Brucella are category B infectious agents that can be aerosolized for biological warfare. As part of the structural genomics studies at the Seattle Structural Genomics Center for Infectious Disease (SSGCID), FolM alternative dihydrofolate reductases 1 from Brucella suis and Brucella canis were produced and their structures are reported. The enzymes share ∼95% sequence identity but have less than 33% sequence identity to other homologues with known structure. The structures are prototypical NADPH‐dependent short‐chain reductases that share their highest tertiary‐structural similarity with protozoan pteridine reductases, which are being investigated for rational therapeutic development.